Modified gallium-indium-tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection
Through the combination of gallium indium tin liquid alloy and nickel powder and brass powder, an efficient anti-bite agent was prepared, which solved the problems of unstable performance and poor conductivity of existing anti-bite agents in high temperature environments, and realized the threaded pair Low friction, versatility and wide applicability.
Patent Information
- Application Number
- CN202411162877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-01-03
AI Technical Summary
The existing anti-bite agents have unstable performance in high temperature, high humidity or chemical corrosion environments, high procurement costs, risk of supply chain breakage, and poor conductivity, resulting in weak electromagnetic shielding capabilities.
Using gallium indium tin liquid alloy as the matrix, nickel powder and brass powder are added to form a modified gallium indium tin liquid alloy multi-function anti-bite agent, which is prepared by mixing evenly and heating in a water bath to form a low melting point, high conductivity and High-flow liquid metal film reduces thread pair friction and improves loosening performance.
Significantly reduce the friction coefficient of thread pairs, improve the loosening cycle of thread pairs, reduce the probability of bite, enhance the conductivity and thermal conductivity, and is suitable for fastener connections of titanium alloys, stainless steel, high-temperature alloys and other materials, avoid bite problems, and in industry It is widely used in equipment, automobiles and construction fields.
Smart Images

Figure CN119242077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fastener coatings, and in particular relates to a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, and is suitable for preventing the connection of titanium alloy, high-temperature alloy, and stainless steel fasteners from seizure. Background Art
[0002] Threaded connections have the advantages of simple form, stable connection, and easy disassembly. They are widely used in detachable fastening connection environments; threaded transmission is also a common transmission method in industry. In industrial applications, threaded contacts often cause thread jamming or seizure (collectively referred to as "seizure" in this article). Bolt seizure will affect equipment operation, increase maintenance difficulty, and reduce work efficiency. Improper handling may even cause major safety accidents and economic losses. Therefore, it is necessary to conduct in-depth research on the thread seizure problem and improve the seizure performance of fasteners.
[0003] A lot of research has been conducted on bolt seizure at home and abroad, and the causes of bolt seizure have been attributed to: problems with the processing of the thread itself, improper operation during the installation and removal of the bolt, problems with the bolt material, the working environment of the threaded connection, and the coating of the threaded contact surface. Currently, the most commonly used thread contact surface coating measures to improve the bolt seizure performance are to apply lubricants and anti-seizure agents. The most commonly used anti-seizure agent on the market is Loctite's 77124 nickel-based anti-seizure agent, which is mainly composed of hydrogen heavy base oil, hydrogenated petroleum heavy alkane fraction, nickel powder, graphite powder, aluminum powder, etc. In the face of high temperature, high humidity or chemical corrosion environmental conditions, the anti-seizure agent can maintain stable performance, which helps to reduce the maintenance frequency of equipment and reduce failures in the production process. In actual applications, the anti-seizure agent has the following disadvantages:
[0004] 1) Due to the problem of independent control of the anti-seizure agent, its procurement cost and the costs related to inventory management and waste disposal are high. At the same time, the use of such commercial products may also face the risk of supply chain disruptions and price fluctuations.
[0005] 2) The main component of the anti-seizure agent is mineral oil, which has poor electrical conductivity. Therefore, it often makes it impossible to maintain electrical continuity between the bolts and nuts, becoming a weak point in electromagnetic shielding capability.
[0006] Taking these advantages and problems into consideration, the present invention uses gallium-indium-tin liquid alloy as a matrix to develop an anti-seize agent with excellent anti-seize performance, good high temperature resistance and good conductivity, so as to achieve autonomous control of the anti-seize agent. Summary of the invention
[0007] In order to overcome the deficiencies in the prior art, the inventors conducted intensive research and provided a modified gallium indium tin liquid alloy multifunctional anti-seize agent suitable for fastener connection, which meets the requirements of excellent anti-seize performance, good high temperature resistance and good conductivity, thereby completing the present invention.
[0008] The technical solution provided by the present invention is as follows:
[0009] In a first aspect, a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection includes: components having the following mass percentages:
[0010] Gallium, indium, tin liquid alloy 75% to 95%;
[0011] Nickel powder 3% to 10%;
[0012] Brass powder 2%~15%.
[0013] In combination with the first aspect, the gallium-indium-tin liquid alloy comprises 65wt% to 70wt% gallium, 19wt% to 23wt% indium and 7wt% to 16wt% tin.
[0014] In combination with the first aspect, the gallium-indium-tin liquid alloy has the following components: 66wt% to 69wt% gallium, 20wt% to 22wt% indium, and 9wt% to 14wt% tin.
[0015] In combination with the first aspect, the gallium-indium-tin liquid alloy has the following components: 67wt% to 69wt% gallium, 21wt% to 22wt% indium, and 9wt% to 12wt% tin.
[0016] In combination with the first aspect, the particle size of the nickel powder is 1 μm to 5 μm; the particle size of the brass powder is 1 μm to 5 μm.
[0017] In a second aspect, a method for preparing a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection is provided, wherein the gallium indium tin liquid alloy is added into a container, and brass powder and nickel metal particles are added into the gallium indium tin liquid alloy in proportion and stirred thoroughly until the powder and the gallium indium tin liquid alloy are thoroughly mixed. Preferably, after the gallium indium tin liquid alloy is added into the container, it is heated in a water bath, and the gallium indium tin liquid alloy is stirred thoroughly using a stirrer.
[0018] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection provided by the present invention has the following beneficial effects:
[0019] (1) The present invention provides a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, which can reduce the friction coefficient of the thread pair. The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut is used as the research object. The application of the anti-seizure agent can significantly increase the slope of the torsion-tension relationship curve, and the application of the anti-seizure agent can effectively reduce the friction coefficient of the thread pair;
[0020] (2) The present invention provides a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, which can improve the anti-loosening performance of threaded pairs. The threaded pair of GH4169 bolts and GH2132 silver-plated self-locking nuts was used as the research object. The application of the anti-seizure agent can significantly improve the loosening cycle of the threaded pair;
[0021] (3) The present invention provides a modified gallium indium tin liquid alloy multifunctional anti-seize agent suitable for fastener connection, which can reduce the probability of thread pair seizure. PH-13 bolts and GH4169 wedge nuts were used as research objects. After repeated tightening and loosening, the nuts were cut open and the morphology was observed using an electron microscope. It was observed that under dry friction conditions, the deformation of the meshing thread was more serious, and the plastic deformation area of the tooth top was very large. Obvious plowing groove-like friction marks and materials torn by adhesive wear were visible, and block-like built-up edges formed inside the nut gap. After the anti-seize agent was applied, the deformation of the tooth top was significantly reduced, the nut thread surface was clean and tidy, and only strip-like plowing grooves existed on the nut surface. No obvious adhesive wear phenomenon was observed. This shows that after the anti-seize agent is applied, the seizure performance of the thread pair is significantly improved;
[0022] (4) The present invention provides a modified gallium indium tin liquid alloy multifunctional anti-seize agent suitable for fastener connection. The anti-seize agent formula is suitable for the connection of stainless steel, high-temperature alloy, and titanium alloy fasteners. It can be promoted for threaded connections in industrial equipment, automobiles, construction and other fields, and can effectively avoid the problem of seizure. At the same time, the anti-seize agent has the characteristics of low melting point, good electrical conductivity and thermal conductivity, high fluidity, etc., and has good compatibility with fasteners of various materials such as titanium alloy, stainless steel, and high-temperature alloy, and can be widely used in other threaded connections or threaded transmission fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of preparation of gallium-indium-tin liquid alloy solution;
[0024] Figure 2 This is a test diagram of the affinity of gallium-indium-tin liquid alloy and powder mixture on a titanium plate;
[0025] Figure 3 The friction coefficient of the fastener under different pressures and speeds when no anti-seize agent is used;
[0026] Figure 4The friction coefficient of the fastener under different pressures and rotation speeds when using gallium-indium-tin liquid alloy;
[0027] Figure 5 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 0.5g of white copper powder;
[0028] Figure 6 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 0.9g of white copper powder;
[0029] Figure 7 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 1.6g of white copper powder;
[0030] Figure 8 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 0.3g of brass powder;
[0031] Fig. 9 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 0.7g of brass powder;
[0032] Fig.10 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 1.1g of brass powder;
[0033] Fig.11 The friction coefficient of the fastener under different pressures and speeds when using 10g of gallium-indium-tin liquid alloy + 0.8g of nickel powder;
[0034] Fig.12 The friction coefficient of the fastener under different pressures and speeds when using 10g of gallium-indium-tin liquid alloy + 1.6g of nickel powder;
[0035] Fig.13 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 0.6g of bronze powder;
[0036] Fig.14 The friction coefficient of the fastener under different pressures and rotation speeds when using 10g of gallium-indium-tin liquid alloy + 1.2g of bronze powder;
[0037] Fig.15 The results of loosening tests when different particle powders are added to the GaInSn liquid alloy;
[0038] Fig.16 The friction coefficient is compared with that of the anti-seize agent prepared in Example 1.
[0039] Fig.17Comparison of loosening cycles with and without the anti-seizure agent prepared in Example 1;
[0040] Fig.18 Comparison of the contact surface morphology of the thread pair with and without the anti-seizure agent prepared in Example 1. DETAILED DESCRIPTION
[0041] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0042] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.
[0043] The present invention provides a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, comprising the following components in percentage by mass:
[0044] Gallium, indium, tin liquid alloy 75% to 95%;
[0045] Nickel powder 3% to 10%;
[0046] Brass powder 2%~15%.
[0047] In a preferred embodiment, the modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection includes the following components in percentage by weight:
[0048] Gallium, indium, tin liquid alloy 75% to 90%;
[0049] Nickel powder 5% to 10%;
[0050] Brass powder 5%~15%.
[0051] In a further preferred embodiment, the modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection includes the following components in percentage by mass:
[0052] Gallium, indium, tin liquid alloy 75% to 85%;
[0053] Nickel powder 6% to 10%;
[0054] Brass powder 9%~15%.
[0055] In a preferred embodiment, the particle size of the nickel powder is 1 μm to 5 μm.
[0056] In a preferred embodiment, the particle size of the brass powder is 1 μm to 5 μm. The particle sizes of the nickel powder and the brass powder should not affect the fastening function of the fastener thread while achieving their respective functions, and should not cause damage to the fastener thread. Taking both into account, the particle sizes of the nickel powder and the brass powder are determined to be 1 μm to 5 μm.
[0057] Gallium indium tin alloy has the advantages of low melting point, high electrical conductivity, high surface tension, low toxicity and corrosion resistance. The present invention uses it as the main component and adds other minerals to form a layer of liquid metal film with fluidity between the metal interface layers, which plays a role in absorbing friction heat and avoiding direct contact of fasteners during the tightening process, thereby preventing the fasteners from biting. After a large number of tests, a gallium indium tin alloy containing 62wt% to 70wt% gallium, 18wt% to 25wt% indium and 5wt% to 20wt% tin was selected. The alloy in this state can remain liquid above -19°C, thereby ensuring that there is a liquid flow layer between the contact surfaces of the fasteners when used under normal temperature conditions and high temperature conditions. The basic formula is prepared as follows: Figure 1 shown.
[0058] Preferably, the composition of the gallium-indium-tin liquid alloy is: 65wt%-70wt% gallium, 19wt%-23wt% indium and 7wt%-16wt% tin.
[0059] More preferably, the composition of the gallium-indium-tin liquid alloy is: 66 wt% to 69 wt% gallium, 20 wt% to 22 wt% indium and 9 wt% to 14 wt% tin.
[0060] Most preferably, the composition of the gallium-indium-tin liquid alloy is: 67wt%-69wt% gallium, 21wt%-22wt% indium and 9wt%-12wt% tin, such as 68.5wt% gallium, 21.5wt% indium and 10wt% tin.
[0061] With gallium-indium-tin liquid alloy as the core, add different additive particles, including nickel powder, white copper, titanium carbide, aluminum oxide, glass powder, nano silicon oxide, indium powder, boron carbide, etc., and stir them thoroughly (see Figure 2 ), the mixture was coated on a titanium plate for testing. The test results are as follows Figure 3 As shown, the ease of mixing and affinity with the metal surface are used as evaluation indicators for preliminary component screening. At the same time, considering that metal nickel has good chemical stability, high hardness, good high temperature strength, good plasticity, and high compressive strength, it has better anti-adhesion and anti-bite properties. At the same time, nickel powder is very easy to mix with liquid metal, so nickel powder is selected as one of the additives. Compared with nickel powder, copper alloy powder has softer hardness and stable chemical properties, which can reduce the wear of nickel powder on the contact surface of fasteners. At the same time, it can also be fully mixed with liquid alloy and can be used as an additive. Therefore, the additive particles initially selected are nickel powder and copper alloy powder.
[0062] The effect of adding different proportions of additives to the basic formula on the friction coefficient of fasteners was studied through repeated friction tests. The test was carried out on an MVF-1A friction and wear tester. The friction form was cone friction. The test force was 50N and 100N respectively; the speed was 100r / min, 200r / min, 400r / min; the running-in time was 1min). The effect of adding different proportions of additives to the basic formula on the anti-loosening performance of fasteners was studied through a lateral vibration test (GB / T10431-2008 Fastener lateral vibration test method). The initial preload was 10kN and the lateral periodic force was 2kN. The addition of additives is shown in Table 1, and the test results are shown in Figure 3 and Fig.15 As shown. Through the test results, it can be seen that the friction coefficient can be increased by adding a small amount of nickel powder. Too much nickel powder will cause the alloy to be squeezed out of the contact surface, thereby reducing the friction coefficient. Therefore, a small amount of nickel powder can be added as a grinding agent. Various copper alloy powders have little effect on the friction coefficient. At the same time, brass powder has better performance in anti-seizure. Combined with the test results, the optimal ratio of anti-seizure agent components is given.
[0063] Table 1 Test results of different anti-seize agent ratios
[0064]
[0065] The present invention also provides a method for preparing a modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, comprising: adding the gallium indium tin liquid alloy into a container, heating it in a water bath to 60°C to 80°C, and using a stirrer for high-speed stirring to form a basic solvent; adding brass powder and nickel metal particles into the basic solvent in sequence according to the above proportions and stirring thoroughly until the powder and the gallium indium tin liquid alloy are fully mixed.
[0066] Example
[0067] Example 1
[0068] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, the preparation method comprising the following steps:
[0069] Adding gallium-indium-tin liquid alloy (68.5 wt% gallium, 21.5 wt% indium and 10 wt% tin) into a container, heating to 60° C. in a water bath, and stirring at high speed using a stirrer to form a base solvent;
[0070] 6 g of brass powder (particle size 1 μm to 5 μm) and 4 g of nickel metal particles (particle size 1 μm to 5 μm) were sequentially added to 40 g of the base solvent and stirred thoroughly until the powder and liquid metal were fully mixed.
[0071] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut is taken as the research object. The torsion-tension relationship curves of the thread pair with and without self-prepared anti-seizure agent are shown in Figure 2. Fig.16 As shown, it can be seen that coating the anti-seize agent can significantly increase the slope of the torsion-tension relationship curve, so coating the anti-seize agent can effectively reduce the friction coefficient of the thread pair.
[0072] Taking the thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut as the research object, the lateral load vibration test of the thread pair without coating and coated with self-prepared anti-seizure agent under different lateral forces was completed. The test results are as follows: Fig.17 As shown, it can be seen that applying the anti-seizure agent can significantly increase the loosening cycle of the thread pair.
[0073] The PH-13 bolt and GH4169 wedge nut were used as the research objects. After repeated tightening and loosening, the nuts were cut open and the morphology was observed using an electron microscope. Fig.18 As shown in the figure, it is observed that under dry friction conditions, the meshing screw teeth are severely deformed, the plastic deformation area of the tooth top is very large, and obvious plowing-shaped friction marks and adhesive wear and tearing of materials can be seen. Blocky built-up edge is formed inside the nut gap. After the anti-seize agent is applied, the deformation of the tooth top is significantly reduced, the nut thread surface is clean and tidy, and only strip-shaped plowing grooves exist on the nut surface. No obvious adhesive wear phenomenon is observed. This shows that after the anti-seize agent is applied, the thread pair's seizure performance is significantly improved.
[0074] Example 2
[0075] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, the preparation method comprising the following steps:
[0076] Adding gallium-indium-tin liquid alloy (68.5 wt% gallium, 21.5 wt% indium and 10 wt% tin) into a container, heating to 60° C. in a water bath, and stirring at high speed using a stirrer to form a base solvent;
[0077] 7.5 g of brass powder (particle size 1 μm to 5 μm) and 5 g of nickel metal particles (particle size 1 μm to 5 μm) were sequentially added to 37.5 g of the base solvent and stirred thoroughly until the powder and the liquid metal were fully mixed.
[0078] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. According to the measured torsion-tension relationship curves of the thread pair with and without coating of self-prepared anti-seize agent, it can be seen that coating of anti-seize agent can significantly increase the slope of the torsion-tension relationship curve. Therefore, coating of anti-seize agent can effectively reduce the friction coefficient of the thread pair.
[0079] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. The lateral load vibration test of the thread pair without coating and coated with self-prepared anti-seize agent under different lateral forces was completed. The test results show that the coating of the anti-seize agent can significantly improve the loosening cycle of the thread pair.
[0080] The PH-13 bolt and GH4169 wedge nut were used as the research objects. After repeated tightening and loosening, the nut was cut open and the morphology was observed with an electron microscope. After the anti-seizure agent was applied, the deformation of the tooth top was significantly reduced, the nut thread surface was clean and tidy, and only strip-shaped furrows existed on the nut surface. No obvious adhesive wear phenomenon was observed. This shows that after the anti-seizure agent was applied, the thread pair's seizure performance was significantly improved.
[0081] Example 3
[0082] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, the preparation method comprising the following steps:
[0083] Adding gallium-indium-tin liquid alloy (68.5 wt% gallium, 21.5 wt% indium and 10 wt% tin) into a container, heating to 60° C. in a water bath, and stirring at high speed using a stirrer to form a base solvent;
[0084] 4.5 g of brass powder (particle size 1 μm to 5 μm) and 3 g of nickel metal particles (particle size 1 μm to 5 μm) were sequentially added to 42.5 g of the base solvent and stirred thoroughly until the powder and the liquid metal were fully mixed.
[0085] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. According to the measured torsion-tension relationship curves of the thread pair with and without coating of self-prepared anti-seize agent, it can be seen that coating of anti-seize agent can significantly increase the slope of the torsion-tension relationship curve. Therefore, coating of anti-seize agent can effectively reduce the friction coefficient of the thread pair.
[0086] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. The lateral load vibration test of the thread pair without coating and coated with self-prepared anti-seize agent under different lateral forces was completed. The test results show that the coating of the anti-seize agent can significantly improve the loosening cycle of the thread pair.
[0087] The PH-13 bolt and GH4169 wedge nut were used as the research objects. After repeated tightening and loosening, the nut was cut open and the morphology was observed with an electron microscope. After the anti-seizure agent was applied, the deformation of the tooth top was significantly reduced, the nut thread surface was clean and tidy, and only strip-shaped furrows existed on the nut surface. No obvious adhesive wear phenomenon was observed. This shows that after the anti-seizure agent was applied, the thread pair's seizure performance was significantly improved.
[0088] Example 4
[0089] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, the preparation method comprising the following steps:
[0090] Adding gallium-indium-tin liquid alloy (67 wt% gallium, 21 wt% indium and 12 wt% tin) into a container, heating to 60° C. in a water bath, and stirring at high speed using a stirrer to form a base solvent;
[0091] 6 g of brass powder (particle size 1 μm to 5 μm) and 4 g of nickel metal particles (particle size 1 μm to 5 μm) were sequentially added to 40 g of the base solvent and stirred thoroughly until the powder and liquid metal were fully mixed.
[0092] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. According to the measured torsion-tension relationship curves of the thread pair with and without coating of self-prepared anti-seize agent, it can be seen that coating of anti-seize agent can significantly increase the slope of the torsion-tension relationship curve. Therefore, coating of anti-seize agent can effectively reduce the friction coefficient of the thread pair.
[0093] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. The lateral load vibration test of the thread pair without coating and coated with self-prepared anti-seize agent under different lateral forces was completed. The test results show that the coating of the anti-seize agent can significantly improve the loosening cycle of the thread pair.
[0094] The PH-13 bolt and GH4169 wedge nut were used as the research objects. After repeated tightening and loosening, the nut was cut open and the morphology was observed with an electron microscope. After the anti-seizure agent was applied, the deformation of the tooth top was significantly reduced, the nut thread surface was clean and tidy, and only strip-shaped furrows existed on the nut surface. No obvious adhesive wear phenomenon was observed. This shows that after the anti-seizure agent was applied, the thread pair's seizure performance was significantly improved.
[0095] Example 5
[0096] A modified gallium indium tin liquid alloy multifunctional anti-seizure agent suitable for fastener connection, the preparation method comprising the following steps:
[0097] Adding gallium-indium-tin liquid alloy (69 wt% gallium, 22 wt% indium and 9 wt% tin) into a container, heating to 60° C. in a water bath, and stirring at high speed using a stirrer to form a base solvent;
[0098] 6 g of brass powder (particle size 1 μm to 5 μm) and 4 g of nickel metal particles (particle size 1 μm to 5 μm) were sequentially added to 40 g of the base solvent and stirred thoroughly until the powder and liquid metal were fully mixed.
[0099] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. According to the measured torsion-tension relationship curves of the thread pair with and without coating of self-prepared anti-seize agent, it can be seen that coating of anti-seize agent can significantly increase the slope of the torsion-tension relationship curve. Therefore, coating of anti-seize agent can effectively reduce the friction coefficient of the thread pair.
[0100] The thread pair of GH4169 bolt and GH2132 silver-plated self-locking nut was taken as the research object. The lateral load vibration test of the thread pair without coating and coated with self-prepared anti-seize agent under different lateral forces was completed. The test results show that the coating of the anti-seize agent can significantly improve the loosening cycle of the thread pair.
[0101] The PH-13 bolt and GH4169 wedge nut were used as the research objects. After repeated tightening and loosening, the nut was cut open and the morphology was observed with an electron microscope. After the anti-seizure agent was applied, the deformation of the tooth top was significantly reduced, the nut thread surface was clean and tidy, and only strip-shaped furrows existed on the nut surface. No obvious adhesive wear phenomenon was observed. This shows that after the anti-seizure agent was applied, the thread pair's seizure performance was significantly improved.
[0102] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0103] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.
Claims
1. An anti-seizure agent suitable for fastener connection, characterized in that: The following components are included in percentage by mass: Gallium, indium, tin liquid alloy 75% to 95%; Nickel powder 3% to 10%; Brass powder 2%~15%.
2. The anti-seizure agent suitable for fastener connection according to claim 1, characterized in that: The components of the gallium-indium-tin liquid alloy are: 65wt%-70wt% gallium, 19wt%-23wt% indium and 7wt%-16wt% tin.
3. The anti-seizure agent suitable for fastener connection according to claim 1, characterized in that: The components of the gallium-indium-tin liquid alloy are: 66wt%-69wt% gallium, 20wt%-22wt% indium and 9wt%-14wt% tin.
4. The anti-seizure agent suitable for fastener connection according to claim 1, characterized in that: The components of the gallium-indium-tin liquid alloy are: 67wt%-69wt% gallium, 21wt%-22wt% indium and 9wt%-12wt% tin.
5. The anti-seizure agent suitable for fastener connection according to claim 1, characterized in that: The particle size of the nickel powder is 1 μm to 5 μm.
6. The anti-seizure agent suitable for fastener connection according to claim 1, characterized in that: The particle size of the brass powder is 1 μm to 5 μm.
7. A method for preparing an anti-seizure agent suitable for fastener connection according to any one of claims 1 to 6, characterized in that: Add gallium indium tin liquid alloy into a container, add brass powder and nickel metal particles into the gallium indium tin liquid alloy in proportion and stir thoroughly until the powder and the gallium indium tin liquid alloy are fully mixed.
8. The method for preparing the anti-seizure agent suitable for fastener connection according to claim 7, characterized in that: Also includes: After the gallium indium tin liquid alloy is added into the container, it is heated in a water bath and the gallium indium tin liquid alloy is fully stirred using a stirrer.
Citation Information
Patent Citations
Liquid metal lubricant using micro-nano powder as additive, and preparation method thereof
CN109022110A
Wear-resistant anti-seizing composite material, wear-resistant anti-seizing composite board and preparation method thereof
CN109047776A
High temperature resistance adhesive coating for nickel-based alloy fastener and preparation method thereof
CN109207989A
High-performance and multi-scale lubrication gallium-based liquid metal lubricant and preparation method thereof
CN114621809A
Gallium-based liquid metal thermal interface material capable of being cured at low temperature and preparation method of gallium-based liquid metal thermal interface material
CN115232603A
